Sinergi Pemerintah Daerah dalam Kebijakan Penurunan Kekerasan Berbasis Gender di Provinsi Lampung - Rahmiyanita Hakim (Public Service and Governance Journal, 2026)
Gender based violence against women and children in Lampung Province represents a multidimensional issue that poses serious challenges to human development and the achievement of the Sustainable Development Goals (SDGs). Although various regulations and programs have been implemented such as Gender Mainstreaming (PUG), Gender Responsive Budgeting (ARG), and local innovations like TAPIS Village and space together with Indonesia (RBI) their implementation remains largely sectoral and lacks systemic coordination. This policy paper employs a descriptive qualitative approach combined with public policy analysis to identify the root cause, namely the absence of an integrated policy framework that ensures cross-sectoral synergy in addressing gender based violence. Data were collected through interviews with key stakeholders and document studies of regional and national planning instruments, including the RPJMD, RENSTRA, and relevant regulations. The analysis reveals that weak inter-agency coordination, limited use of gender-disaggregated data, low human resource capacity, and the absence of an incentive sanction mechanism are the main obstacles to effective policy implementation. Three policy alternatives were formulated: the development of a gender responsive complaint platform for violence against women and children, the integration of gender-disaggregated data systems, and the adoption of a reward punishment system for government agencies. Based on Dunn’s six evaluation criteria, the establishment of a gender-responsive complaint platform is considered the most effective and is recommended as a strategic solution. This policy is expected to strengthen institutional synergy, enhance intervention effectiveness, and foster an inclusive and sustainable protection system for women and children in Lampung Province.